2010
DOI: 10.1038/ejcn.2010.117
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and measures of cognitive function in healthy older European adults

Abstract: Background/Objectives: Data from human studies that have investigated the association between vitamin D status and cognitive function in elderly adults are conflicting. The objective of this study was to assess vitamin D status (reflected by serum 25-hydroxyvitamin D (25(OH)D)) in older European subjects (n ¼ 387; aged 55-87 years) and examine its association with measures of cognitive function. Subjects/Methods: Serum 25(OH)D was assessed using enzyme-linked immunosorbent assay, whereas measures of cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 40 publications
5
42
0
Order By: Relevance
“…functioning are the cognitive domains most associated with vitamin d status. thus, our results support and extend those of previous findings in studies using lower vitamin d cut-off values and different population groups, including older adults 7,8 , europeans 6,8 , and men 6 . Specifically, among elders (65-99 yrs) enrolled in the naMe Study, vitamin d levels >50 nmol/l were associated with better performance on several tasks of executive functioning/attention, even after controlling for several potential confounders.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…functioning are the cognitive domains most associated with vitamin d status. thus, our results support and extend those of previous findings in studies using lower vitamin d cut-off values and different population groups, including older adults 7,8 , europeans 6,8 , and men 6 . Specifically, among elders (65-99 yrs) enrolled in the naMe Study, vitamin d levels >50 nmol/l were associated with better performance on several tasks of executive functioning/attention, even after controlling for several potential confounders.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, among middle-aged and older (40-79 yrs) european men as part of the european Male aging Study 6 , those with low vitamin d levels (<35 nmol/l) performed worse on digit symbol substitution, after correcting for multiple variables. in healthy european adults (55-87 yrs) enrolled in the Zenith study 8 , vitamin d levels were significantly correlated with performance on the CantaB® Spatial Working Memory task, as we found in our cross-sectional analysis in winter. While reverse causation (i.e., that cognitive impairment leads to low vitamin d levels due to lack of outdoor activity) has been questioned regarding cross-sectional dementia case control results, it seems less likely in this relatively healthy sample with no overt dementia or physical impairment.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In another population-based study with 752 women aged ≥75 years from the 'Epidemiologie de l'Osteoporose' (EPIDOS) cohort, after adjustment for multiple confounders, an association of deficient vitamin D concentration (<10 ng/ml) with cognitive impairment assessed by Pfeiffer Short Portable Mental State Questionnaire was reported (OR 1.99; 95% CI 1.13-3.52) [27]. An Irish multicenter study among 387 elderly healthy Etgen/Sander/Bickel/Sander/Förstl participants reported an association of vitamin insufficiency and impaired spatial working memory, especially in women [28]. Annweiler et al [29] found in 288 older patients of a French geriatric acute care unit a significant association between severe vitamin D deficiency (<10 ng/ml) and moderately severe to severe dementia (OR 2.57; 95% CI 1.05-6.27).…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
“…Low levels of 25(OH)D have been associated with cognitive impairment among women in several cross-sectional studies [6,7], and among men in a large study including 3,133 non-institutionalized males [8]. Among women and men receiving home services, low levels of 25(OH)D were associated with dementia and cerebrovascular pathology [9], and among older patients at a memory clinic, hypovitaminosis D was associated with executive dysfunction [10].…”
Section: Introductionmentioning
confidence: 99%